MediKit : IoT Based Smart Healthcare System for Effective Supervision of Patient - Surya Tej, Mahankali; Ameet Chavan, Dr (International Journal of Engineering and Technology, 2018)
Medikit - An IoT healthcare system is developed for patients, hospitals and care centers that regularly supervise the health condition and checks whether the patient has taken the prescribed medicine. The proposed work monitors patientâ€™s vitals such as pulse rate and body temperature on real time basis. Such information will be used by the doctor to diagnose the patient remotely and prescribe optimum medication dose. Further, the Medikit system apart from collecting the data ensures that patient has taken the medicine on time.Â For the proposed system the authors have used Bluetooth Technology to send sensor data to a Smartphone and also to Cloud Service Platform for archiving and analysis. The information available on the Cloud can be supervised by the doctor by using a Mobile application. The mobile application also supports scheduling of medicines as per doctorâ€™s prescription in the medical box. The comprehensive system developed, to the best of authorâ€™s knowledge, is low cost, efficient and service oriented as compared to the traditional healthcare practices and other eHealth solutions discussed.Â